Exhumation of an anatectic complex by channel flow and extrusion tectonics: structural and metamorphic evidence from the Porto–Viseu Metamorphic Belt, Central-Iberian Zone - M. Bento dos Santos, Telmo (2021)
Abstract: Structural and metamorphic analyses of the Porto–Viseu Metamorphic Belt (PVMB), an anatectic complex located in the Central-Iberian Zone (CIZ), Iberian Variscan Massif, constrain the kinematic features of the polyphase Variscan deformation, as well as the boundary conditions associated with the exhumation and emplacement of the belt onto the CIZ’s lower-grade metasediments. A sharp metamorphic contrast is evident between the lowest grade rocks of the anatectic complex—garnet-staurolite mylonitic schists with a minimum metamorphic peak at P = 5.7 kbar and T = 635 °C—and the host chlorite-biotite metasediments of the CIZ. Additional P–T estimates for metatexites in the PVMB provided P = 7.6–7.9 kbar and T = 770–810 °C, confirming high-grade metamorphic peak conditions. The temperature jump between the anatectic complex and the low-grade host rocks exceeds 400 °C if the anatectic core of the belt (metatexites, diatexites, and S-type granites) is considered, implying a vertical difference of 10–17 km. The PVMB is limited in the NE by a D2 shear zone displaying normal kinematics, which has been explained so far by extensional tectonics. However, the SW boundary is limited by a D2 shear zone showing reverse kinematics. This pair of coeval and antithetical ductile shear zones bordering the PVMB, associated with the increase of the metamorphic grade towards the axial domain of the belt, is consistent with anatectic channel flow, followed by extrusion tectonics of the PVMB within an overall D2 compressive setting.